Location Based Service for Important Locations in the Paser Belengkong District - Azahari; Tommy Bustomi; Angga Setiawan (TEPIAN, 2023)
Location-based service systems or better known as Location-Based Services (LBS) are information services in the form of geographic information accessed using a smartphone via a mobile network connection for precise mapping. This research focuses on profile information and routes for office locations, places of worship, health, schools, emergency places, markets, sports facilities and infrastructure, companies and ATMs in Paser Belengkong District with location points that utilize the Location Manager Application Programming Interface technology. (API maps) and Location Provider (API Location) from Google. The data collection method used was interviews by asking questions related to important location data in Paser Belengkong District. By way of observation, namely by making direct observations of the villages in Paser Belengkong District. In this research the system development method uses the waterfall and the testing techniques used are Black Box and Beta Testing. The supporting software used is Android Studio, Xampp, Sublime Text, Google Maps and software design using the Unified Modeling Language (UML) modeling system, Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams. Test results by utilizing Location Based Service Technology which combines Geographic Information System, Internet Service